Iodine increases pulmonary type I interferon responses and decreases covid-19 disease severity: Results from an open label randomized clinical trial - René Traksel; Jasper Broen; Arjen van Henten; Marc Königs; Arjun Raj; Laura van Eyndhoven; Richard Verheesen (PLoS ONE, 2026)
Objective To investigate whether oral treatment with 12.5 mg iodine additional to standard of care is effective in reducing mortality and clinical deterioration of patients hospitalized with COVID-19. Methods We performed a single center, randomized clinical trial (EudraCT 2020-001852-16) in which patients with severe covid-19 in need of hospitalization were randomized in two groups. The first group received 12.5 mg oral iodine for 8 days, the second group did not receive iodine next to the standard of care. Primary endpoints were deterioration of disease defined as transfer from the ward to the intensive care unit (ICU) or death. Next to these parameters we collected parameters in line with the recommendations made by the WHO in the early days of the pandemic. On these additional datasets we performed an exploratory analysis and investigated possible confounders and trends. The inclusion phase of the study was between October 2020 and April 2022. Finally, in vitro validations were performed. Results Outcomes from 141 participants were analyzed, revealing no significant differences in mortality or transfers to intensive care between the iodine-treated group (67 patients) and the control group (74 patients). In an exploratory analysis we found that patients randomized to receive oral iodine had a significantly shorter stay at the ICU ( p = 0.016). In vitro validations proved increased virus-induced type I interferon responses upon iodine administration in pulmonary cells. Conclusion These findings suggest that while iodine does not reduce mortality or ICU admissions, it may enhance antiviral immunity through increased type I interferon responses, contributing to shorter ICU stays in COVID-19 patients. The role of iodine in enhancing IFN-I mediated antiviral immunity warrants future research. Registration of trial: EudraCT Number: 2020-001852-16. https://www.clinicaltrialsregister.eu/ctr-search/search?query=2020-001852-16 Sponsor name: Maxima Medical Center. Date of Registration: April 1 st 2020.